The tropical environment and malaria in southwestern Nigeria, 1861 "“ 1960 - Adetiba, Adedamola Seun (Rhodes University, Faculty of Humanities, Department of History, 2019)
This thesis is a social history of malaria in southwestern Nigeria. It contributes to the burgeoning literature in the historiography of medicine, specifically the medicine and empire debate. Key to the issues raised in this thesis is the extent to which the limitations in colonial medical policies, most especially malaria control programmes, inspired critical and ingenious responses from African nationalists, doctors, patients, research volunteers, and indigenous medical practitioners. Challenged by a wide range of diseases and a paucity of health facilities and disease control schemes, African rural dwellers became medical pluralists in the ways they imagined and appropriated ideas of Western medicine alongside their indigenous medical practices. Beginning with a detailed historical exploration of the issues that informed the introduction of curative and preventive medicine in southwestern Nigeria, this thesis reveals the focus of colonial medicine. It exposes the one-sided nature of medical services in colonial spaces like southwestern Nigeria and the ways it shaped multifaceted responses from Africans, who were specifically side-lined till the 1950s when the rural medical service scheme was introduced. The focus of colonial medicine is drawn from relatively rich but often subjective historical evidence, such as a plethora of official reports of the department of medical and sanitary services, official correspondences within the colonial government in Lagos and Nigeria, and between the colonial government and the colonial office in the United Kingdom. Details of African responses to medical policies were garnered from newspaper publications and correspondences between the African public and the colonial government in Lagos. They reveal very interesting details of the ways Africans imagined, reimagined, and appropriated malaria control ideas and schemes. The central argument in this thesis is that attempts to control malaria in southwestern Nigeria till the 1950s, were shaped by a single concern to ameliorate the implications of the disease on the colonial state. It argues that this one-sided nature of malaria control programme informed the basis for medical pluralism in most rural spaces where African communities became patrons and sponsors of Western medicine and at the same time custodians of their indigenous medical practices. The series of justifications for the sustenance of these services were reinforced on the basis of the failure of the colonial state to guarantee the health needs of their colonial subjects. The aim of the thesis is to reinforce arguments that portray colonial medicine as a "tool of empire" but goes a bit further to explain the extent to which Africans related to this reality. It states quite categorically that Africans were not docile and silent, but that they acted decisively in ways that suited their varied interests and courses.
Keywords: Diseases and history -- Africa; Diseases and history -- Nigeria; Medical anthropology -- Africa; Medical anthropology -- Nigeria; Malaria -- Social aspects -- Nigeria; Malaria -- Nigeria -- History; Nigeria -- History; Imperialism -- Health aspects; Medicine -- Colonies -- Great Britain -- History